Model Calculation of the Piezoelectric Coefficient of Hexagonal 2D Materials. Issue 2 (13th December 2018) - Lew Yan Voon, Lok C.; Willatzen, Morten; Wang, Zhong‐Lin
Abstract: A quantum‐mechanical microscopic model of the piezoelectric effect in 2D materials is developed. The piezoelectric coefficient requires the calculation of an internal atomic displacement and an effective piezoelectric charge. The internal displacement is obtained from minimizing the strain energy given by a Keating‐like model, while the effective charge takes into account the atomic displacements and also a redistribution of the electronic charge; a bond‐orbital model is used to compute the latter. The final theory only requires atomic energies and the elasticity constants of the materials as input parameters. The piezoelectric coefficients of a number of II‐VI, III‐V and IV‐IV materials that could stably form in the planar hexagonal structure are computed; results for the IV‐IV materials are obtained for the first time. Abstract : An atomistic study of piezoelectric coefficients of 2D materials is presented using a Keating‐like model . Internal atomic displacements and a bond‐orbital model are used to compute the effective charge. The piezoelectric coefficients of a number of II‐VI, III‐V, and IV‐IV materials are computed. Results for the IV‐IV 2D materials are obtained for the first time.